Silent hypoxia is not an identifiable characteristic in patients with COVID-19 infection. (June 2022) - Plummer, Nicholas Russell; Fogarty, Andrew; Shaw, Dominick; Card, Timothy; West, Joe; Crooks, Colin
Abstract: Background: We aimed to assess whether asymptomatic ("happy") hypoxia was an identifiable physiological phenotype of COVID-19 acute respiratory distress syndrome (ARDS), and associated with need for ICU admission. Methods: We performed an observational cohort study of all adult patients admitted with hypoxaemic respiratory failure to a large acute hospital Trust serving the East Midlands, UK. Patients with confirmed COVID-19 were compared to those without. Physiological response to hypoxaemia was modelled using a linear mixed effects model. Results: Of 1, 586 patients included, 75% tested positive for SARS-CoV-2. The ROX index was 2.08 min −1 lower (1.56–2.61, p < 0.001) in the COVID-19 cohort when adjusted for age and ethnicity, suggesting an enhanced respiratory response to hypoxia compared to the non-Covid-19 patients. There was substantial residual inter- and intra-patient variability in the respiratory response to hypoxaemia. 33% of the infected cohort required ICU, and of these 31% died within 60 days. ICU admission and mortality were both associated with an enhanced respiratory response for all degrees of hypoxaemia. Conclusions: Patients with COVID-19 display a more symptomatic phenotype in response to hypoxaemia than those with other causes of hypoxaemic respiratory failure, however individual patients exhibit a wide range of responses. As such although asymptomatic hypoxaemia may be a phenomenon in any individual patient with hypoxaemic respiratory failure, it is no more frequently observed in those with SARS-CoV-2 infection than without. Highlights: Patients with and without COVID-19 display a wide variation in their physiological response to hypoxaemia. COVID-19 patients are no more physiologically "happy" in response to hypoxaemia, and actually have higher respiratory rates for any given SpO2 /FiO2 Ratio. Decreasing physiological "happiness" in response to hypoxaemia is associated with worse outcomes in COVID-19. TThe ROX index may be a simple tool to discriminate patients at risk of adverse outcomes in COVID-19 from bedside observations.